Laboratory analysis of local clayey soils with inclusions of shredded rubber materials - Borcelis, Ian J.
Waste rubber tires have been long contributing to solid waste problems in the environment. Comprising of 3.03 million tons by weight that are either buried or burned in US alone, such a huge amount of waste must be re-used one way or another. The research focuses on the disposal of shredded waste rubber materials whilst observing geotechnical application for soil improvement. Shredded rubber tires were used as an additive to be mixed with local soil. Samples were prepared from soil with varying amount of shredded rubber material content and also varying dimensions of the fiber material. Local clayey soils were used for the analysis of the effect of the fiber materi al in shear strength and the load bearing capacity of the improved soil. The samples were subjected to California Bearing Ratio test for the loadbearing capacity and unconfined compression test for its shear strength. The research has observed an increase in both load-bearing capacity and shear strength in CBR test and UCT having a maximum increase in strength of 41.46% and 91.28% respectively. The said increase in CBR was observed using 0.8cm x 3cm rubber chips and 1.2cm x 3cm rubber chips for UCT.